Protection of Bombax Ceiba by Revealing their Fungal Endophytic Diversity and Therapeutic Applications: Life Sciences-Microbiology for health care - Rohit Shankar Mane; Ankala Basappa Vedamurthy (International Journal of Life Science and Pharma Research, 2022)
The objective of the present research investigation was to protect Bombax ceiba by revealing their endophytic fungi diversity for disease management. In the present research investigation, a total of 64 fungal endophytes were purified and, Aspergillus tamari was identified as a core fungal endophyte. The fungus showed the highest average linear growth rate of 6.2 mm/day and isolation frequency at 80% on tomato dextrose agar with white or dark brown or black or purple-brown to yellowish-green color variations with mycelial growth in between 65 mm to 90 mm on the media and 8 to 31 numbers of spores/ microscopic field. Further, the fungus revealed 2.86 g/100g of total wet biomass and 0.25 g/100g of the dried biomass of corn bran with 5.30 g/100ml of the aqueous crude extract in solid-state fermentation. Mycochemical screening of the crude extract showed alkaloids, terpenoids, steroids, tannins, saponins, flavonoids, phenols with 29.0060±0.03223 mg of total phenolic and 12.2549±0.02345 mg of flavonoids content. Thin layer chromatography was used to get purified potent spots of alkaloids [0.29], flavonoids [0.41] terpenoids [0.15] and saponins [0.91]. The fungus produced chitinase, amylase, protease, and cellulases enzyme. Further the aqueous crude extract worked as an agent of antioxidant in the FRAP at the rate of 1.2407±0.00702 while PM at 0.7983±0.00351, antimicrobials against E. coli (100mg/ml at the rate of 16.3±0.57) and Aspergillus niger (100mg/ml at the rate of 20.5 ± 0.24), and in anthelmintic activity, extract induced paralysis in earthworms within 3 minutes and death in 8 minutes. It is concluded that the Bombax ceiba has the potential to purify the potent fungal endophytes and their bioactive compounds that may be helpful to evaluate in vivo models against different diseases.